A 17 year old with isolated proximal tibiofibular joint arthritis - Canna Scott W; Chauvin Nancy A; Burnham Jon M (BMC, 2013)
Abstract The proximal tibiofibular joint (TFJ) is rarely affected in rheumatic diseases, and we frequently interpret pain of the lateral knee as the result of overuse or trauma. Nonetheless, the TFJ is a synovial joint that communicates with the tibiofemoral joint in a proportion of patients. While proximal TFJ arthritis has been rarely associated with existing spondyloarthritis, isolated TFJ arthritis as the presenting manifestation of spondyloarthritis has not yet been described. Here, we report the clinical and radiographic presentation of an adolescent with chronic proximal TFJ arthritis heralding spondyloarthritis highly suggestive of ankylosing spondylitis.